An Example of a Multiplayer Serious Game on 3D Sandpile Model - Hayk E. Nahapetyan (Изд-во НАН РА)
Purpose of this paper is to consider cellular automata models as a base of a type of serious games.As an example of cellular automata, the Abelian Sandpile model on 3D graphs has been chosen. Moreover, a networked multiplayer gaming environment (SandGame) has been developed using .Net and C# language.
Keywords: Mathematics; Computer software